Development of Health Profile Compilation Based on Digital Applications - Firmansyah, Firmansyah (Jurnal KESANS : Kesehatan dan Sains, 2025)
This policy paper explores the development and implementation of a health profile system powered by digital applications. In many regions, the manual process of compiling health profiles hampers timely decision-making and reduces data accuracy. A transition to a digital, application-based approach is crucial for enhancing data quality, accessibility, and integration across health sectors. This paper identifies current challenges, presents policy alternatives, and recommends the establishment of a centralized, modular, and cloud-based platform. The initiative aims to strengthen evidence-based policymaking and accelerate the digital transformation of Indonesia's healthcare system.